The Acceleration of Immigrant Unhealthy Assimilation - Osea Giuntella; Luca Stella (Institute for the Study of Labor (IZA), 2016)
It is well-known that immigrants tend to be healthier than US natives and that this advantage erodes with time spent in the US. However, we know less about the heterogeneity of these trajectories among arrival cohorts. Recent studies have shown that later arrival cohorts of immigrants have lower entry wages and experience less economic assimilation. In this paper, we investigate whether similar cohort effects can be observed in the weight assimilation of immigrants in the US. Focusing on obesity, we show that more recent immigrant cohorts arrive with higher obesity rates and experience a faster "unhealthy assimilation" in terms of weight gain.
Keywords: J15; I10; 330; health assimilation; healthy immigrant effect